Sequential and simultaneous application of phages in the inactivation of Escherichia coli and its effect on antibiotic resistance - Henriques, Ana Maria Vieira (2023)
Escherichia coli stands as a primary bacterium accountable for moderate and severe infections in both hospital and community settings, primarily owing to the emergence of antibiotic-resistant strains. Increased infections caused by antibiotic-resistant E. coli strains drive up mortality rates and healthcare expenditures. Hence, there is a need for effective methods to manage E. coli infections. Among the most promising strategies is applying phage therapy to prevent and treat these infections. Bacteriophages are bacterial viruses known for their high specificity, safety for human cells, great versatility, ease of isolation, and characterisation. In general, phage therapy is a straightforward and cost-effective treatment. However, using a single-phage treatment for infections caused by various bacterial strains may not be efficient due to the phage's specificity. An effective solution is the use of phage cocktails, which consist of a mixture of different phages. This approach is versatile, capable of addressing single and multiple bacterial infections, and can help mitigate the development of phage resistance. In recent years, research focusing on the potential of phage cocktails as biological control agents against E. coli is growing. In this study, we evaluated the impact of simultaneous and sequential administration of phages on E. coli inactivation. We also assessed these phages' influence on bacterial susceptibility to specific antibiotics. The findings from this study indicate that employing phage cocktails, whether administered simultaneously or sequentially, presents a promising alternative for E. coli inactivation. Furthermore, it can be inferred that phages have the potential to alter bacteria, eventually reducing their antibiotic resistance.